Single Session Multimodal Approach to Treat Acne Scars Using Subcision, Fractional CO2, and Stromal Vascular Fraction Injection - Aakash Gupta; Madura Chandraiah; Chandrashekar Byalakere Shivanna (Clinical Dermatology Review)
Background: Acne scars are commonly seen in the young population affecting quality of life. Treatment requires different modalities which can span over few months to years. A multimodal approach is required to treat various types of scars in a single session. Aims and Objectives: The aim of this study was to assess the efficacy and safety of multimodal approach for acne scars using blunt subcision, fractional CO2 laser, and stromal vascular fraction (SVF) injection. Materials and Methods: The study included 20 patients with atrophic scars. All the patients were treated with subcision using Taylor Acne Liberator™ after injection of tumescent anesthesia, CO2 laser, and SVF injection. Patients were followed up at intervals of 5 days, 1 month, and 3 months. Side effects of the procedure were noted. Results: The mean improvement in acne scars was 3.2 after 3 months of procedure. This indicates the role of multimodal approach in treating various types of scars in single sessions. Seventy percent of patients were extremely satisfied with the procedure. Conclusion: The multimodal approach gives excellent results in the management of acne scars and can be used when patients cannot visit frequently for treatment.